Explaining Animal Abuse Among Adolescents: The Role of Speciesism - Bègue, Laurent (Journal of interpersonal violence, 2022)
Animal abuse is considered a significant marker of violence towards humans, and understanding its determinants is important. In this first large-scale survey on adolescent animal abuse carried out in France, we introduced and tested the relative explanatory power of a new variable potentially involved in animal abuse: speciesism, defined as the belief that humans are intrinsically more valuable than individuals of other species. In a school sample composed of 12,344 participants aged 13?18 years, we observed that 7.3% of participants admitted having perpetrated animal abuse. Consistent with existing studies, cats and dogs were the animals most often abused. Animal abuse was a solitary behavior approximately half of the time, and in 25% of instances it involved only another person. A multivariate logistic regression revealed that animal abuse was more frequent among males and that it occurred more often among adolescents with less positive family climate, lower support from friends, lower attachment to school, and with higher anxio-depressive symptomatology. As implied by the generalized deviance hypothesis, animal abuse was related to more deviant behavior such as drunkenness and bullying. Moreover, this study showed for the first time that animal abuse was higher among adolescents who endorsed speciesist attitudes. These results suggest that beyond psychopathological factors, normative beliefs regarding the value of animals and their human use may also be involved in animal mistreatment.